(untitled) (Jóvenes en la Ciencia, 2025)
Molds of the genus Aspergillus contaminate cereal, legume, and oilseed crops, both in the field and during storage when environmental conditions permit, causing losses and risk of mycotoxins. The present study aimed to evaluate the effect of microwave treatments on sunflower seeds and pasilla peppers against Aspergillus flavus. Microwave treatments were applied until the target temperature of 60°C was reached, followed by cooling with air. Effectivity of 100% was reached reducing the A. flavus population by 4 log cycles. Meanwhile, in sunflower seeds, population was reduced by 1 log cycle. Microwave treatment did not affect the moisture content of pasilla pepper, and had no effect on the moisture content, water activity and color of sunflower seeds (p>0.05).